PERLAKUAN AKUNTANSI ASET BIOLOGIS PADA PERUSAHAAN PANGAN ISLAMI SEKTOR AGRIKULTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Gardina Aulin Nuha; Juli Rima Afiani; Nindi Nadia Yurisma (Universitas Muhammadiyah Jember, 2023)
This study aims to analyze how the accounting treatment for biological asset in Islamic food agricultural company sector listed in the Indonesia Stock Exchange. This study is a cualitative study with descriptive analyse. The study data used secondary data in annual report of sample companies in 2020. The sample 8 companies with sampling technique using purposive sampling. The results of the first study indicate that the accounting recognition of biological assets is in accordance with PSAK 69, where the biological assets of most companies are recognized as current assets. The results of the second study indicate that the accounting measurement of biological assets is in accordance with PSAK 69, where the company's biological assets are recognized at fair value at the end of the financial reporting period. The results of the third study indicate that the disclosure of biological assets is in accordance with PSAK 69. The conclusion of the study is that the accounting treatment of companies in the Islamic food agriculture sector is in accordance with PSAK 69.